Cover Picture: Solid‐State Molecular Nanomagnet Inclusion into a Magnetic Metal–Organic Framework: Interplay of the Magnetic Properties (Chem. Eur. J. 2/2016). Issue 2 (3rd December 2015) - Mon, Marta; Pascual‐Álvarez, Alejandro; Grancha, Thais; Cano, Joan; Ferrando‐Soria, Jesús; Lloret, Francesc; Gascon, Jorge; Pasán, Jorge; Armentano, Donatella; Pardo, Emilio
Abstract : Solid‐state incorporation of a single‐ion magnet (SIM) within the pores of a magnetic 3D metal–organic framework (MOF) in a single‐crystal to single‐crystal process has been demonstrated. The resulting host–guest supramolecular aggregate affords the first deep study on the interplay of the internal magnetic field of the MOF and the slow magnetic relaxation of the SIM allowing the observation of a partial suppression of the quantum‐tunneling effects operative in the SIM. More information can be found in the Full Paper by D. Armentano, E. Pardo et al. onpage 539 ff.